Infecciones Hospitalarias/ Malagón-Londoño, Gustavo - Malagón-Londoño, Gustavo. Hernndez Esquivel, Libardo (1995)
El objetivo de este libro, consiste en fomentar la prevención, y ahorrar en coste sanitario.